2012
DOI: 10.1093/ndt/gfs470
|View full text |Cite
|
Sign up to set email alerts
|

Decline in renal functioning is associated with longitudinal decline in global cognitive functioning, abstract reasoning and verbal memory

Abstract: Early detection of mild to moderate kidney disease is an important public health concern with regard to cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
5
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 52 publications
4
85
5
5
Order By: Relevance
“…In our study, there was a trend for a 1 ml/min per 1.73 m 2 per year eGFR decline (approximately double the median annual eGFR decline) to be associated with lower DSST scores in the cohort. Two population-based studies with unimpaired renal function and a low prevalence of diabetes reported that only an eGFR decline of .3-4 ml/min per 1.73 m 2 per year was significantly associated with cognitive decline (5,42).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there was a trend for a 1 ml/min per 1.73 m 2 per year eGFR decline (approximately double the median annual eGFR decline) to be associated with lower DSST scores in the cohort. Two population-based studies with unimpaired renal function and a low prevalence of diabetes reported that only an eGFR decline of .3-4 ml/min per 1.73 m 2 per year was significantly associated with cognitive decline (5,42).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown a progressive decline in cognitive functions with progressive renal failure (Kurella et al 2005b;Davey et al 2013). Emotional changes, anxiety and depression have also been reported in cases of chronic renal failure (Montinaro et al 2010).…”
Section: Locomotor Exploratory and Emotional Activitymentioning
confidence: 99%
“…In line with this, Davey et al [23] could not show an association between baseline eGFR as indicator of kidney function and change in cognitive function also assessed with a comprehensive neuropsychological test battery at baseline and 5-years follow-up, but between decreases in eGFR and decreases in cognitive performance, with about 37% of CKD patients experiencing a clinically relevant deterioration of eGFR defined by >3 mL/min/1.73 m²/year, which was twice the frequency observed in the NT CVD cohort. Also in accordance with this finding of high relevance of tight control of kidney function and CKD-associated risk factors and diseases for the prevention of progression of cognitive deficits is the positive effect of dialysis and transplantation therapy on cognition [24].…”
Section: Introductionmentioning
confidence: 67%